La Perception Des Instances De Régulation (Tribunal Coutumier, Sous-Préfecture, Tribunal Moderne) Du Règlement Des Conflits Fonciers En Pays Aboure - Rodrigue, N’guessan Kodjo (European Scientific Journal, ESJ, 2018)
The aim of the study is to identify the social factors that make up the Aboure's perception of regulatory bodies in the management of land conflicts in the Abouré populations of the sub-prefecture of Bonoua (Côte d'Ivoire). Reasoned sample of investigation is the size of 40 individuals. The investigation, namely, the direct observation and the inquiry-interrogation, concerned both the administrative actors (Ministry, Sub-prefects, Prefects, etc.). and villagers (village rural management committees, traditional chiefdoms, the royal court, presidents of youth and women, farmers, foreign communities). The data, obtained and analyzed qualitatively and quantitatively, show that the conflicting aspects of the perception of land regulators have criminal consequences. Key words: perception, credibility, management, court, custom, organ, ethnicity, cultural reference.